2020
DOI: 10.1016/j.bja.2020.05.054
|View full text |Cite
|
Sign up to set email alerts
|

High-dose versus low-dose tranexamic acid for paediatric craniosynostosis surgery: a double-blind randomised controlled non-inferiority trial

Abstract: Background: Tranexamic acid (TXA) reduces blood loss and transfusion in paediatric craniosynostosis surgery. The hypothesis is that low-dose TXA, determined by pharmacokinetic modelling, is non-inferior to high-dose TXA in decreasing blood loss and transfusion in children. Methods: Children undergoing craniosynostosis surgery were enrolled in a two-centre, prospective, double-blind, randomised, non-inferiority controlled trial to receive high TXA (50 mg kg À1 followed by 5 mg kg À1 h À1 ) or low TXA (10 mg kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 28 publications
(28 reference statements)
0
54
0
Order By: Relevance
“…Two studies calculated the cost associated with TXA use per patient versus the cost of blood product transfusions. 17,18 The Risk of Bias (RoB) for 5 studies was judged to be low and one was judged to be probably low. The details of the RoB for the studies included are shown in Table 1.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies calculated the cost associated with TXA use per patient versus the cost of blood product transfusions. 17,18 The Risk of Bias (RoB) for 5 studies was judged to be low and one was judged to be probably low. The details of the RoB for the studies included are shown in Table 1.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Two studies calculated the cost associated with TXA use per patient versus the cost of blood product transfusions. 17,18…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…A few randomised studies reported the difference in postoperative seizure fit in TXA treated patients and placebo-treated patients. Hooda et al 3 reported lower incidence in the TXA group compared with the placebo group in intracranial meningioma (3.3% vs 6.7%) patients while in other randomised controlled trials of paediatric craniosynostosis and tumour resection, no seizures were observed 9 10 26. Nevertheless, the incidence of seizure attacks was measured as the secondary outcome and the sample size of both studies was relatively small.…”
Section: Introductionmentioning
confidence: 97%
“…Tranexamic acid (TXA), an antifibrinolytic drug widely used for haemostasis, inhibits plasminogen activation and stabilises the blood clot by reversibly binding to the lysine residues on plasminogen, hence reducing intraoperative bleeding 7. TXA is used as a bolus ranging from 10 to 50 mg/kg, followed by a continuous infusion ranging from 1 to 5 mg/kg/hour until the end of the procedures in a variety of neurosurgical procedures 3 8–10. Unfortunately, the risk of postoperative seizures remains uncertain, and restricts the routine use of TXA in neurosurgery, though it is a safe and effective means to reduce operative blood loss and blood transfusion rates in cardiac, pulmonary, trauma, obstetric, spinal and orthopaedic surgery 11–14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation